1992
DOI: 10.1055/s-2006-961701
|View full text |Cite
|
Sign up to set email alerts
|

Volatile Constituents ofArtemisia annua

Abstract: Planto Med. 58, Supplement issue 11992Posters Under the homogeneous field conditions, significant differencies in all the examined parameters were recorded for the ten tested cultivars. The Egyptian cultivar confirms its good yields and its very high estragole content, beside the low fenchone content; only the Turkish cultivar yielded a higher amount of essential oil per hectare than the Egyptian one, but also this oil was poor in fenchone. The Polish cultivar presented the highest fenchone content, built was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1994
1994
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…Artemisia ketone, camphor, 1,8-cineole, α-pinene, β-caryophyllene, germacrene-D, p -cymene, o -cymol, and artemisia alcohol were reported as the major components (≥10%) of the essential oils of А. annua and are different from species growing in other geographic locations. 1,2,13,15 -54 Also, bisabolol, bisabolol oxide B 26,27 , and α-cubebene 18 were found as major components of the A. annua essential oils. Analyses in the published research data showed that many species of the Artemisia genus, including A. annua, A. vulgaris, A. diffusa, A. santonicum, A. spicigera, A. afra, A. asiatica, A. austriaca, and A. pedemontana , contain bornane derivatives (camphor, borneol and bornyl acetate) and 1,8-cineole as the major components.…”
Section: Resultsmentioning
confidence: 97%
“…Artemisia ketone, camphor, 1,8-cineole, α-pinene, β-caryophyllene, germacrene-D, p -cymene, o -cymol, and artemisia alcohol were reported as the major components (≥10%) of the essential oils of А. annua and are different from species growing in other geographic locations. 1,2,13,15 -54 Also, bisabolol, bisabolol oxide B 26,27 , and α-cubebene 18 were found as major components of the A. annua essential oils. Analyses in the published research data showed that many species of the Artemisia genus, including A. annua, A. vulgaris, A. diffusa, A. santonicum, A. spicigera, A. afra, A. asiatica, A. austriaca, and A. pedemontana , contain bornane derivatives (camphor, borneol and bornyl acetate) and 1,8-cineole as the major components.…”
Section: Resultsmentioning
confidence: 97%